Investigation of the oxidation behavior and high oxidation-resistant mechanism of Ti(C, N)-based cermets. (December 2020) - Zhang, M.M.; Jiang, Y.; Lin, N.; Kang, X.Y.; Yan, Y.; Huang, J.H.; Liu, Y.; Qiu, S.; He, Y.H.
Highlights: Oxidation kinetics of conventional and Cr-doped Ti(C, N)-based cermets at 800 °C are compared Both cyclic and continuous oxidation mass changes of Ti(C, N)-based cermets are measured Different oxide layers are arranged according to the stability of oxidation products The addition of alloyed Cr prevents the formation process of W-rich oxide film The formed CrWO4 reduces ion mobility in the internal oxide region Abstract: The oxidation kinetics and mechanisms of Ti(C, N)-based cermets have been studied systematically in this work. The continuously stable NiCo2 O4 -spinel and (Co, Ni)WO4 film are the keys to providing essential reassurance for low oxidation rates in conventional cermets. After the addition of alloyed Cr, the oxidation weight gain of the cermet significantly decreased. The superior oxidation-resistant performance of Cr-doped cermet was a result of the formation of Cr(W, Mo)O4, which showed high stability and a high oxygen migration barrier energy. The distribution of Cr(W, Mo)O4 in the intermediate oxide layer reduced the ions mobility during the oxidation process.